PENERAPAN MODEL PEMBELAJARAN ASSURANCE, RELEVANCE, INTERST, ASSESSMENT, SATISFACTION (ARIAS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IVA SD NEGERI 183 PEKANBARU - Zhandy, Muthia Afrilla; Alpusari, Mahmud; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: This research is motivated because of the low results of fourth grade students to learn science, with the average obtained is 69.36. This research is a classroom action research (PTK), which consists of two cycles, held on second semester of 2015/2016. These research subjects are 39 students. This study aims to improve learning outcomes IVA grade science students of SD Negeri 183 Pekanbaru by applying the learning model Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS). The research instrument consists of learning tools and data collection instrument. Data analysis technique used is the analysis of observation sheets and student learning outcomes. Mechanical analysis of data on the activities of teachers and students is based on the observation sheet during the implementation of the action. Data analysis showed completeness of student learning outcomes of student learning outcomes, the frequency distribution for the highest value range and improving student learning outcomes. Based on the analysis of the observation sheet activities of teachers and students saw an increase include: the activities of teachers in the first cycle reaches 70%, the second cycle is 95% while in the student activity cycle I reached 65%, the second cycle reaches 95%. Analysis of the data showed an increase in student learning outcomes include: mastery learning in the first cycle 19, the second cycle 32, the frequency distribution for the highest value range for each of the first cycle of 48.72%, 82.05% second cycle. This indicates that the application of learning models ARIAS can improve learning outcomes IVA grade science students of SD Negeri 183 Pekanbaru.Keywords: model ARIAS, learning outcomes IPA